A Review on Bioactive Compounds and Pharmacological Properties of Cleome rutidosperma DC: A review on Cleome rutidosperma - Nguyen, Trang (Journal of Tropical Life Science, 2023)
Cleome rutidosperma DC., a species of flowering plant in the Cleomaceae family, is commonly known as